(untitled) (Symposium on Natural and Applied Sciences, 2026)
In recent years, artificial intelligence (AI) has become an innovative tool in medical education and practice. However, the inappropriate use of AI or its application without critical thinking may negatively affect students’ knowledge quality and clinical reasoning skills. Studies indicate that improper use of AI reduces active learning and critical thinking among medical students, increases passivity, and raises the risk of decision-making based on inaccurate or unverified information. At the same time, proper integration of AI can enhance educational effectiveness, although clear scientific guidelines and ethical standards are required.